Patient safety culture and associated factors among nurses working at public hospitals in Gamo Zone, Southern Ethiopia - Bereket Beyene Shashamo; Gesila Endashaw Yesera; Meseret Girma Abate; Wubshet Estifanos Madebo; Lankamo Ena Digesa; Tamiru Chonka Choramo (BMC, 2023)
Abstract Background Patient safety culture is the prevention of errors and adverse effects to patients associated with health care delivery. It is a vital component in the provision of quality care. In healthcare settings where there is a safety culture, the people (providers, staff, administrators, and patients/families) are engaged, encouraged, and supported to make care safer. Though it is an essential component in the provision of quality care, little is known about its level, contributory, and hindering factors from the nurses' perspectives. This study aimed to assess patient safety culture and associated factors among nurses working at public Hospitals in Gamo Zone, Southern Ethiopia. Methods This institution-based cross-sectional study was conducted among 398 nurses working at public hospitals in Gamo Zone. Data were collected by pretested, well-structured self-administered questionnaire from June 1 to 30, 2022. The collected data were checked, coded, and entered into Epi-data version 4.6.0.2 and were exported to SPSS version 25 for analyses. Bivariable and multivariable logistic regression was done to identify independent factors associated with patients' safety culture. Results This study revealed that 202(50.8%), 95% CI: (46%-56%) of the participants had indicated good patient safety culture. From factors analysis, having an educational status of a bachelor's degree and above [AOR = 2.26, 95%CI: (1.13-4.52)], working in a surgical ward [AOR = 5.48, 95%CI: (1.96-15.34)], not being blamed when medical errors happened [AOR = 3.60, 95%CI: (1.82 - 7.14)], and working 40 up to 49 h per week [AOR = 0.30, 95%CI: (0.13 - 0.74)] were identified to be significantly associated with good patient safety culture. Conclusion Based on the study findings, it could be observed that good patient safety culture was indicated only by half of the study participants. Implementing actions that support dimensions of patient safety culture, and creating opportunities for continuous educational advancement is recommended. Moreover, Hospital administrators, nurses' directors, and healthcare policy-makers should work in collaboration to improve the patient safety culture, and also it would be better to create a blame-free environment to promote event reporting practices.